Impact assessment of input and output market development interventions by IPMS Project: The case of Gomma Woreda - Tolemariam, A. (Haramaya University, 2010)
The study evaluates the ex-post impact of input and output market development interventions on total household net income, intensity of input use and productivity, marketed surplus and market orientation behavior of the households. Moreover, the study has assessed the change in the institutional and organizational aspect of market of the woreda due to market interventions. For quantitative analysis both program participant and non participant respondents were drawn and cross-sectional survey data were collected from 200 households in Gomma woreda. Propensity score matching method was employed to analyze the impact of the project interventions quantitatively. This method was checked for covariate balancing with a standardized bias, t-ratio, and joint significance level tests. Furthermore, sensitivity analysis of the estimated participation effect to unobserved selection bias was checked using the Rosenbaum bounds procedure. Results show that participation in market development interventions has a significant, positive and robust impact on the outcome variables measured using different indicators. However, for some outcome variable indicators such as household income from coffee commodity, input use for apiculture and fruit production, productivity of improved hives, land allocation for coffee and number of hives possessed by the household are positive but statistically insignificant. The sensitivity analysis also shows that the impact result estimates are insensitive to unobserved selection bias. The qualitative assessment shows that the main changes were the private sector (including agro-industry) involvement in supplying inputs by opening alternative village shops as well as the development of community based input supply system, linking the farmers/private traders to the input importer and potential buyers and innovative credit provision specifically meant to enhance input and output marketing interventions. Furthermore, different platforms specifically for the apiculture and sheep fattening has been set by the community which help them to abide by. To hedge against the risk involved in sheep fattening practice, a kind of community based insurance program was established. In order to alleviate access to market, establishing farmers’ cooperatives and linking this cooperatives or individual farmers to potential buyers (including exporters) was done. The thesis finally discusses these results in detail and draws some recommendations.